2016
DOI: 10.1002/anie.201602397
|View full text |Cite
|
Sign up to set email alerts
|

Advanced High‐Voltage Aqueous Lithium‐Ion Battery Enabled by “Water‐in‐Bisalt” Electrolyte

Abstract: A new super-concentrated aqueous electrolyte is proposed by introducing a second lithium salt. The resultant ultra-high concentration of 28 m led to more effective formation of a protective interphase on the anode along with further suppression of water activities at both anode and cathode surfaces. The improved electrochemical stability allows the use of TiO2 as the anode material, and a 2.5 V aqueous Li-ion cell based on LiMn2 O4 and carbon-coated TiO2 delivered the unprecedented energy density of 100 Wh kg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
459
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(484 citation statements)
references
References 22 publications
4
459
1
2
Order By: Relevance
“…[217][218][219][220][221][222] Undoubtably, the most obvious benefit of this optimized electrolyte system is an increased variety of available cathode/anode materials comparing with the traditional type of ARLBs. However, only a few studies have been reported on ARLBs with hierarchitectures, especially constructed by 2D nanomaterials.…”
Section: Aqueous Rechargeable Lithium Batteriesmentioning
confidence: 99%
“…[217][218][219][220][221][222] Undoubtably, the most obvious benefit of this optimized electrolyte system is an increased variety of available cathode/anode materials comparing with the traditional type of ARLBs. However, only a few studies have been reported on ARLBs with hierarchitectures, especially constructed by 2D nanomaterials.…”
Section: Aqueous Rechargeable Lithium Batteriesmentioning
confidence: 99%
“…Most recently, however, several groups have reported that certain kinds of aqueous electrolytes without free water molecule have wider electrochemical window and reasoned that the water molecules hydrated to lithium ion do not engage in electrochemical decomposition. For example, 21 m lithium bis(trifluoro methanesulfonyl)imide (LiTFSI) aq., 3 21 m LiTFSI + 7 m lithium trifluoromethane sulfonate (LiOTf ) aq., 4 saturated LiNO 3 aq., 5 ]), respectively. In such highly concentrated aqueous Li electrolytes, not only the water activity but also the solubility of the electrode is reduced by water solvation and thick solid electrolyte interface (SEI).…”
Section: Introductionmentioning
confidence: 99%
“…[3] To address these issues, various approaches have been developed. [9] Battery systems using aqueous electrolytes have presented great progress, however there has been little investigation on current collectors for aqueous battery systems. [4] Inorganic solid-state electrolytes have also been investigated to replace organic liquid electrolytes because they are nonflammable and have high enough mechanical strength to prevent dendritic lithium from penetrating the electrolyte.…”
mentioning
confidence: 99%
“…Among various aqueous batteries, lead-acid batteries using sulfuric acid as electrolyte were invented in 1859 and are still widely used in automobiles for starting, ignition, and lighting. [9] Battery systems using aqueous electrolytes have presented great progress, however there has been little investigation on current collectors for aqueous battery systems. An excellent cycling stability can be achieved by eliminating oxygen from electrolyte and modifying electrodes.…”
mentioning
confidence: 99%